Nase zkusenosti s bilaterálním prístupem pri chirurgické lécbĕ primární hyperparatyreózy. (Soubor 222 pacientů operovaných pro primární hyperparatyreózu v letech 1994-2000.) - Adámek, S; Libánský, P; Tvrdon, J; Pafko, P; Broulík, P (Rozhledy v chirurgii, 2002)
Surgical treatment offers a definite cure of patients with primary hyperparathyroidism. When making the diagnosis of primary hyperparathyroidism the success of a surgical solution depends on the experience and judgment of the surgeon. Our experience with 222 operations and re-operations convinced us on the preference of a bilateral approach, i.e. exploration of both sides of the neck. The ectopic localization of the parathyroid glands, the limited possibilities of an unequivocal interpretation of the histological examinations but also the frequent incidence of thyropathies leads the surgeon, in our opinion, to the complete exploration of both sides of the neck within the framework of the primary operation for primary hyperparathyroidism. This approach leads most probably to the best results. We use an aimed unilateral approach only in old patients who are in a very bad condition where we anticipate a benefit from a short operation.
Keywords: paratyreoidektomie; Aged, 80 and over; dospělí; Adult; lidé; Parathyroidectomy; mladiství; Adolescent; senioři nad 80 let; dítě; Child; Aged; Humans; senioři; lidé středního věku; Middle Aged; hyperparatyreóza; Hyperparathyroidism